Ozonolysis of some complex organic substrates in flow - Roydhouse, Mark D.; Motherwell, William B.; Constantinou, Achilleas; Gavriilidis, Asterios; Wheeler, Rob C.; Down, Kenneth D.; Campbell, Ian B. (My University, 2013)
The ozonolysis of several organic substrates to give carbonyl compounds, carboxylic acids and nicotinic acids in flow using a standard lab-scale flow system equipped with a cooled flow cell was examined. Alkyl and aryl alkenes showed good conversion (49-99%) to the corresponding aldehydes and ketones utilising an "in flow" quench of triphenylphosphine. The ozonolysis of either 2 or 3-substituted furans obtained furnished a variety of carboxylic acids including the pharmaceutically important oxetane-3-carboxylic acids in two steps from furan and oxetan-3-one. Substituted benzoic acids were generated with high yields in two steps from aryl iodides. The non-selective ozonolysis of quinolines is known to give 2,3-dicarbonyl substituted pyridines, herein we report the selective ozonolysis of 8-hydroquinoline to give 3-[(1E)-3-oxoprop-1- en-1-yl]pyridine-2-carboxylic acid using flow techniques.
Keywords: Aromatic compounds; Carboxylic acids; Ketones; Organic pollutants; Pyridine